Positron emission tomography imaging of endogenous mu-opioid mechanisms during pain and migraine. (July 2019) - DaSilva, Alexandre F.; Zubieta, Jon-Kar; DosSantos, Marcos F.
Abstract : Abstract: The enormous advancements in the medical imaging methods witnessed in the past decades have allowed clinical researchers to study the function of the human brain in vivo, both in health and disease. In addition, a better understanding of brain responses to different modalities of stimuli such as pain, reward, or the administration of active or placebo interventions has been achieved through neuroimaging methods. Although magnetic resonance imaging has provided important information regarding structural, hemodynamic, and metabolic changes in the central nervous system related to pain, magnetic resonance imaging does not address modulatory pain systems at the molecular level (eg, endogenous opioid). Such important information has been obtained through positron emission tomography, bringing insights into the neuroplastic changes that occur in the context of the pain experience. Positron emission tomography studies have not only confirmed the brain structures involved in pain processing and modulation but also have helped elucidate the neural mechanisms that underlie healthy and pathological pain regulation. These data have shown some of the biological basis of the interindividual variability in pain perception and regulation. In addition, they provide crucial information to the mechanisms that drive placebo and nocebo effects, as well as represent an important source of variability in clinical trials. Positron emission tomography studies have also permitted exploration of the dynamic interaction between behavior and genetic factors and between different pain modulatory systems. This narrative review will present a summary of the main findings of the positron emission tomography studies that evaluated the functioning of the opioidergic system in the context of pain.